Protocolo para la elaboración de guías quirúrgicas impresas en 3d en el laboratorio dental, para colocación de implantes dentales: artículo de revisión - López Silva, Christian Andrés (2025)
Recently with the development of digital dentistry, using CadCam technology we can perform surgical planning, to place dental implants likewise, make the 3D printed surgical guide, it is a biomedical prosthetic device, which helps the implantologist in the rehabilitation on implants and in this way have a minimally invasive surgery, significantly improving the precision and correct accuracy with the placement of dental implants, thus facilitating surgery and reducing working times. Objective: To create a protocol for the development of a surgical guide, 3D printed in the dental laboratory, for implant placement, through a rigorous search of updated literature. Materials and methods: The present article is elaborated with the PRISMA method, with the collection of information, obtained in indexed journals that have a high quartile of publication. The information collected was obtained from different databases such as Google Scholar, ProQuest, Scielo, Pub Med and Science Direct with publication in the last 6 years, in this way it was possible to obtain and compile valid information, according to inclusion and exclusion criteria, where the development of a surgical guide, printed in 3D in the dental laboratory, for the placement of implants is proposed. Results: From a total of 50 articles initially obtained, from which 20 scientific articles were selected for the present protocol, we proceeded to exclude some documents from the database for, being documents without relevant information, for being non- retrievable documents, for being duplicates, for being documents that only contain clinical information without laboratory information, for being another type of study, for the date of publication prior to 2018 and for not being related to the topic. Conclusions: With the collection of the information obtained through the present investigation, it was possible to create a protocol for the development of 3D printed surgical guides in the dental laboratory, for the placement of dental implants.